1988
DOI: 10.1073/pnas.85.3.963
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and phorbol ester stimulate conductive Na+ transport through a common pathway.

Abstract: Insulin stimulates Na+ transport across frog skin, toad urinary bladder, and the distal renal nephron. This stimulation reflects an increase in apical membrane Na+ permeability and a stimulation of the basolateral membrane Na,K-exchange pump. Considerable indirect evidence has suggested that the apical natriferic effect of insulin is mediated by activation of protein kinase C. However, no direct information has been available documenting that insulin and protein kinase C indeed share a common pathway in stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…Insulin (and presumably GH) (58) recently showed that D-sphingosine (100 ,uM) reduces the Na+-transporting stimulation ofinsulin on frog skin, suggesting that at least part of its effects on the membrane Na+ permeability and Na+,K+-exchange pump are mediated by protein kinase C.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin (and presumably GH) (58) recently showed that D-sphingosine (100 ,uM) reduces the Na+-transporting stimulation ofinsulin on frog skin, suggesting that at least part of its effects on the membrane Na+ permeability and Na+,K+-exchange pump are mediated by protein kinase C.…”
Section: Resultsmentioning
confidence: 99%
“…A possible basis for this mimicry of hormones by exogenous phospholipase C lies in the finding that many hormone receptors increase phospholipid turnover, production ofdiacylglycerol, and activation of the calcium-and phospholipid-dependent enzyme, protein kinase C (PKC) (2)(3)(4), and there is indirect evidence for PKC participation in acute metabolic effects of insulin on adipocytes and other cells. Tumor-promoting phorbol esters, which substitute for diacylglycerol in stimulating PKC (3), increase transport of glucose (5-9) and amino acids (7), activate pyruvate dehydrogenase (7), increase lipogenesis (6,8,(9)(10)(11), and stimulate ion transport (12,13). Moreover, insulin has been reported to increase phospholipid metabolism (14)(15)(16) and the formation of diacylglycerol in adipose tissue (17) and in cultured myocytes (17)(18)(19), but there is sharp disagreement on this issue (20,21).…”
mentioning
confidence: 99%
“…The effects of insulin in vitro on epithelial Na ϩ channels appear to be tissue dependent. In amphibian model systems, insulin clearly stimulates ENaCmediated Na ϩ transport as shown in studies of frog skin (28), toad urinary bladder (3,29), and A6 cells (2,9). As discussed above, the rat CCD responds to insulin with an increase in Na-K-ATPase activity.…”
Section: Discussionmentioning
confidence: 88%
“…Insulin stimulates Na-K-ATPase in many cell types including the mammalian cortical collecting duct (CCD) (7,8). The hormone also clearly upregulates the epithelial Na channel (ENaC) in amphibian model tissues, including frog skin (28), toad urinary bladder (3,29), and A6 cells (2,9). However, such effects have not been observed in mammalian kidney tubules (15,34).…”
mentioning
confidence: 95%